Plasma treatment process for accelerating the disintegration of a biodegradable mulch film in soil and compost - Bhattacharya, Swapnil; Kansara, Harshal Jayesh; Lodge, Jeffery; Diaz, Carlos A.; Lewis, Christopher L. (Frontiers in Materials, 2023)
Biodegradable Mulch Films (BMFs) offer a sustainable alternative to traditional non-degradable (Polyethylene) PE mulch films. However, their slow rate of biodegradation can lead to plastics accumulation in soil. In this study, a commercially available BMF based on poly(butylene adipate co-terephthalate) (PBAT) and poly(lactic acid) (PLA) is examined. Here the effects of gliding arc plasma treatment on the bulk and surface properties, as well as its degradation behavior in soil and compost is studied. An increase in surface oxygen containing species and hydrophilicity was observed following plasma treatment. Only a small hydrophobic recovery was noted over 30 days. No changes in the bulk polymer molecular weight or thermal properties following treatment were noted.However, a decrease in mechanical strength was observed following gliding arc plasma treatment. The onset of film fragmentation in both soil and compost occurred earlier for a plasma treated film and we attribute this to an improvement in the initial adhesion of bacteria on the surface.